Bullous pemphigoid and internal diseases - a case-control study - Jedličková, Hana; Hlubinka, Miloslav; Pavlík, Tomáš; Semrádová, Věra; Budinská, Eva; Vlašín, Zdeněk (European journal of dermatology, 2009)
To study associations of bullous pemphigoid (BP) with internal diseases, we conducted a retrospective case control study assessing the frequency of selected diseases - diabetes mellitus, neurological diseases, malignant tumors, benign prostate hyperplasia, hypertension and ischemic heart disease in patients with BP. 89 patients with BP, whose data were retrieved from the register of the Centre of bullous diseases from the period of 1991-2006, were matched with 89 controls of the same age and gender, recruited from patients treated for other skin diseases. The frequency of internal diseases at the time of the onset of BP was evaluated by unconditional logistic regression adjusted for age and gender and maximum likelihood test for contingency tables. Neurological disease was found in 42.7% of the patients and in 19.1% of controls. This difference was statistically significant (p value = 0.001). Moreover, regression analysis has shown that patients with neurological disease in the age group >or= 80 years have significantly higher risk of pemphigoid than patients without neurological disease (odds ratio 10.55; 95% confidence interval 2.68 to 41.49). Most frequent were cerebral stroke in men and dementia in women. For other diseases and other age groups, no statistically significant influence was found.
Keywords: nemoci nervového systému; hypertenze; Female; Myocardial Ischemia; ženské pohlaví; Neoplasms; Nervous System Diseases; nádory; lidé; ischemická choroba srdeční; Aged, 80 and over; hyperplazie prostaty; Hypertension; Male; Pemphigoid, Bullous; Aged; Diabetes Complications; bulózní pemfigoid; lidé středního věku; senioři nad 80 let; Prostatic Hyperplasia; senioři; mužské pohlaví; komplikace diabetu; Middle Aged; Humans